Assessment Changes in Hematological Parameters for Iraqi Individuals That are Working in Petrol Refineries - Athraa Sami (Institute of Medico-legal Publications Pvt Ltd, 2021)
The attention has been increased to assess the hematological toxic effects of petroleum products from refineries especially the volatile chemical contaminants (VCC) like benzene. Petrol pump operators are workers frequently exposed to petroleum products that has been occasionally associated with large incidences of hematological disorders and adverse health effects as a result of damage to the haemopoietic system accompanied by depletion to the bone marrow. This study was made to evaluate the hematological parameters among petrol refinery workers according to the duration of exposure. A cross sectional study was done in Al Najaf -refinery for petrol. It involved 101 petrol pump operators, thirty one (31) healthy male office workers who were considered as the control group and two groups of seventy (70) male petrol pump operators as the study group. The samples of blood were collected from both study and control groups and tested for red blood cells count (RBC), hemoglobin concentration (Hb), white blood cell count (WBC), packed cell volume (PCV) level and platelet count (Plt). Chronic exposure to volatile chemical contaminants has a harmful effects on refinery workers with increasing the risk of developing hematological disorders due to the deleterious effects on the bone marrow